PERSEPSI DAN PERILAKU PENGUNJUNG DALAM MENDUKUNG KEBERLANJUTAN TAMAN WISATA ALAM MANGROVE ANGKE KAPUK JAKARTA - Lenny Yusrini (LPPM and Travel Operation Department Universitas Asa Indonesia, 2018)
In the context of natural tourist attraction, the sustainability principles is a must-implemented attitude. One of the nature-based tourist attractions that Jakarta has is the Taman Wisata Alam (TWA) Mangrove Angke Kapuk in the coast of North Jakarta. This study is aimed to analyze the perception and behaviour of the visitors in supporting the sustainability of the area. A survey was conducted using a questionnaire developed by the underlying theories of perceptions and the five ecotourism principles. Validity and reliability tests were conducted towards 30 respondents and the results showed 3 of 21 items were not valid and were dropped. Data was collected using simple random sampling technique involving 110 respondents. The measurement of the perception and behaviour used mean score and the result was then described qualitatively. The results showed that both visitors perception and behaviour are in the category of “very positive”, which means that the perception and the behaviour of the visitors are supporting the sustainability of the TWA Mangrove Angke Kapuk